Hesitant adopters: An examination of hesitancy among adults in Arkansas who have taken the COVID‐19 vaccine - Pearl A. McElfish; Brett Rowland; Aaron J. Scott; Jennifer A. Andersen; Sheena CarlLee; Joshua C. McKinnon; Sharon Reece; Sandra M. Meredith‐Neve; Michael D. Macechko; Morgan Gurel‐Headley; Don E. Willis (Wiley, 2022)
Abstract Recent research suggests people who report vaccine hesitancy may still get vaccinated; however, little is known about hesitancy among those who chose to vaccinate. The current study focused on individuals who received the coronavirus disease 2019 (COVID‐19) vaccine despite their hesitancy, whom we refer to as "hesitant adopters." With the understanding that vaccine attitudes and vaccine behaviors may or may not be correlated, we examined the prevalence of COVID‐19 vaccine hesitancy among those who have been vaccinated, how COVID‐19 vaccine hesitancy varies across sociodemographic groups, and how COVID‐19 vaccine hesitancy relates to other factors (prior health care access and influenza vaccination behavior over the past 5 years). Random digit dialing of telephone landlines and cell phones was used to contact potential survey respondents, rendering a sample of 1500 Arkansan adults. Approximately one‐third of those who received a COVID‐19 vaccine also reported some level of hesitancy. Among hesitant adopters, 5.3% said they were "very hesitant," 8.8% said they were "somewhat hesitant," and 17.1% said they were "a little hesitant." Black/African American and Hispanic/Latinx respondents reported more hesitancy than White respondents, and female respondents reported greater hesitancy compared to male respondents. Greater hesitancy was associated with non‐metro/rural residence, forgoing health care due to cost, and lower influenza vaccination rates over the past 5 years. Findings suggest those who are hesitant may get vaccinated despite their hesitancy, illustrating the complexity of vaccination behaviors. Prevalence of hesitancy among the vaccinated has implications for communication strategies in vaccine outreach programs and may help to reduce stigmatization of hesitant adopters.